PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PEREDARAN NARKOTIKA - Gusti I Nyoman Irgi Aditya; Rara Amalia Cendhayanie (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The circulation of narcotics in Indonesia has experienced a significant increase. One of the most concerning phenomena is the involvement of children in the narcotics distribution chain, either as couriers or intermediaries. Children, who should be the subject of state protection, are instead being used as tools by narcotics networks that exploit structural weaknesses in the legal and social protection systems. This research was conducted using a normative juridical research method, namely by examining library materials or secondary data. The approaches used are the statute approach and the conceptual approach. The regulation of criminal liability for children in Indonesia is outlined in several laws and regulations, including the 1945 Constitution of the Republic of Indonesia, the Indonesian Criminal Code (KUHP), the 2023 Criminal Code, Law No. 11 of 2012 concerning the Juvenile Justice System, and Law No. 35 of 2014 concerning Child Protection. Legal protection for children involved in narcotics-related criminal acts must still ensure the fulfillment of their rights during sentencing, based on the principle of restorative justice. However, in practice, restorative justice through the implementation of diversion by police investigators, prosecutors, and the courts has not yet been fully optimized. The government and policymakers need to strengthen the implementation of restorative justice principles within the juvenile criminal justice system. It is essential for law enforcement agencies to actively advocate for the rights of children in conflict with the law, especially those involved in narcotics distribution networks.